(untitled) (International Journal of Engineering and Computer Science, 2016)
: Network-based cloud computing is now rapidly expanding all over as an alternative to conventional office-based computing. Cloud computing has become widespread and the energy consumption of the network and computing resources will grow cloud. This happens when there is increasing attention being paid to the need to manage energy consumption across entire information and communications technology (ICT) sector. In the proposed scheme data duplication technology is going to be used which is method of reducing storage needs by eliminating redundant data. This will save a lot of money on storage cost to store the data and on bandwidth costs to move the data. This paper, presents an analysis of energy consumption in cloud computing. The analysis will consider both public and private clouds. Computing tasks are of low intensity or infrequent. Thus, under some circumstances cloud computing may consume more energy than conventional computing where each user performs all computing on their personal computer (PC).